Indonesian Subtitling Translation Techniques in Muhsin and Mahasin Arabic Cartoons: A Descriptive Study Oriented to Newmark Theory - Muhammad Nur Kholis; Dika Ayu; Nadhifa N; Hafidah N; W Hakimmudin; M Luthfi (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
The purpose of the study was to identify and describe the translation techniques, methods and ideologies used in translating Arabic cartoon subtitles Muhsin and Mahasin versions of the Youtube channel SFH channel and describe the quality of the translation as the impact of the techniques, methods, and ideologies applied, in terms of accuracy, acceptance and ,readability. This research uses qualitative approaches using qualitative descriptive methods. Included in the study data are Arabic video subtitles Muhsin and Mahasin, while the data sources are muhsin videos and Mahasin link versions https://youtu.be/PZ3DPvdvVdI. The data collection technique used is scriptwriting. After the data collection process, analysis is also carried out. The findings of the study showed that there are six kinds of translation techniques. Based on the dominant techniques that occur, translators tend to use communicative translation methods and domestication as their ideology. Then, the impact of the application of translation techniques, methods and ideologies on the quality of translation as a whole has accuracy, acceptance, and readability. This shows the quality of good translation.